Liver cirrhosis in Malaysia: Peculiar epidemiology in a multiracial Asian country - Qua, C.S.; Goh, K.L. (Blackwell Publishing, 2011)
Background and Aim: To determine the etiology of liver cirrhosis and risk factors for hepatocellular carcinoma (HCC) in a multiracial Asian population.